Extracorporeal Testicular Ectopia through Inguinal Canal: A Case Report - Haidar AM; Gharmool BM (EL-Med-Pub, 2013)
A preterm (36 week) neonate, presented with his left testicle hanging outside through the inguinal canal. The testicle was pexed in a sub-dartos pouch.